Low genetic diversity and significant structuring in the endangered Mentha cervina populations and its implications for conservation - Rodrigues, Leandra (2014)
Eighteen populations of the endangered aromatic and medicinal plant Mentha cervina (Lamiaceae) were sampled across its natural range, in the western half of the Iberian Peninsula, and inter-simple sequence repeats (ISSRs) markers were used to assess genetic diversity and population structure. M. cervina populations exhibited a relatively low genetic diversity (percentage of polymorphic loci PPB ¼ 14.2–58.3%, Nei’s genetic diversity He ¼ 0.135–0.205, Shannon’s information index I ¼ 0.08 0.33). However, the genetic diversity at species level was relatively high (PPB ¼ 98.3%; He ¼ 0.325; I ¼ 0.23). The results of the analysis of molecular variance indicated very structured populations, with 50% of the variance within populations, 44% among populations and 6% between regions defined by hydrographic basins, in line with the gene differentiation coefficient (GST ¼ 0.532). A Mantel test did not find significant correlation between genetic and geographic distance matrices (r ¼ 0.064), indicating that isolation by distance is not shaping the present genetic structure. The levels and patterns of genetic diversity in M. cervina populations were assumed to result largely from a combination of evolutionary history and its unique biological traits, such as breeding system, low capacity of dispersion, small effective size and habitat fragmentation. The high genetic differentiation among populations indicates the necessity of conserving the maximum possible number of populations. The results also provide information to select sites for ex situ conservation. Optimal harvesting strategies, cultivation and tissue culture should also be developed as soon as possible to guarantee sustainable use of the species under study.